Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

College Students Understanding of Production Management and Master Production Schedule through Using a Real World Tool, Complimented with Company Tours and In- Class Visits, Provides an Excellent Learning Experience at Farmingdale State College - O'Sullivan, Jill (Journal of Systemics, Cybernetics and Informatics, 2015)
Manufacturing is playing a significant role in its re-shoring into America. Companies are grappling with ways to obtain that competitive advantage by distinguishing themselves through their intellectual capabilities, process improvements, technology, people, shop floor management and information flows. The purpose of this paper is to describe the effort at Farmingdale State College to educate our students in understanding Production Management and Master Production Schedule (MPS). We are trying to prepare students for entry into the workforce. By using a Real world ERP tool in the classroom while complimenting this learning with touring local manufacturers who use this tool and having production control experts in our classrooms. [1] The opportunity presents itself for these students to visit real world manufacturers using the same tool these students use in the classroom, the Infor Visual ERP. Each semester students go to a local manufacturer to see how the product is made and the ERP system is used to make it. Each semester a subject matter expert, SME, in manufacturing comes into the class and talks about how they use their ERP to perform their functional responsibilities. Students go into these companies and sit down with these Production Manufacturing and IT SME’s to see how they use the modules in their ERP system from estimating, Production Management, MPS to delivery and payment. From the manufacturing window to the Master Schedule Window students learn from these companies SME’s just how they perform their functions, how they use this tool. Then that is replicated this in the classroom lab assignments for students to better understand Production Management, scheduling and work order integrity. They identify the desired schedule (forecast) and populate a Master Production Schedule. They create a BOM with work orders adding operations and material. The Production Management/Control is the function of directing or regulating the movement of goods through the entire manufacturing cycle from the requisitioning of raw material to the delivery of finished products. (APICS Dictionary 13th Edition) The Master Production Schedule is often a major component of Sales and Operations Management. The purpose of the Master Schedule is to translate the Sales forecast into a Production Plan that must be executed by the organization. The Master Schedule is the demand side of the equation and must represent the customers’ needs. In this way the Master Scheduler can give manufacturing its best chance for success. Master Production Schedule (MPS): The MPS should be closely aligned with the Sales Forecast. Students enter a Sales Forecast into the system similar to what they have seen at the companies. Students see how it is the liaison between the Sales Forecast and a production work order. Its function is to translate the Sales Forecast into a viable production schedule that supports the customer requirements, while taking into account shop floor constraints. The MPS must support the Sales Forecast and customer demand. Students learn the importance of this in their lab assignments. They identify and enter shop floor resources. Students learn that companies should never chase supply they should chase demand and manage supply. Supply can mean, purchased parts, and externally produced parts, internally made items, internal machine or labor constraints. The student’s comprehension of this topic, concept and knowledge is significantly enhanced due to the tours to local manufacturers and the individuals that come into the class to discuss these functional areas and the processes they perform in their organizations.

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed